HUBUNGAN ANTARA FAKTOR RISIKO DENGAN KEJADIAN TB PADA ANAK DI POLIKLINIK ANAK RUMAH SAKIT TK II MOH. RIDWAN MEURAKSA JAKARTA - MuhammD Hafizd Nugroho, (2021)
Pediatric pulmonary tuberculosis is one of the most common chronic infectious diseases in Indonesia, especially in densely populated areas including Jakarta. Children are very at risk of contracting pulmonary tuberculosis, especially if there is contact with infectious pulmonary tuberculosis patients, low immunity factors and bad environmental factors. This study aims to determine what factors are associated with the incidence of tuberculosis in RS Tk.II Moh. Ridwan Meuraksa Jakarta. This type of research is an observational analytic study with a cross-sectional design. A total of 53 samples were selected by purposive sampling. The study was conducted from October 2019 - January 2020. The data was collected by filling out a questionnaire. The independent variable is the factor that affects the incidence of pulmonary tuberculosis in children, the dependent variable is the incidence of pulmonary tuberculosis in children. Data analysis used bivariate and multivariate. The results showed that respondents who suffered from pulmonary tuberculosis were 16 children (30.2%) less than those who did not suffer from pulmonary TB, namely 37 children (69.8%). The results of the Chi-square test showed that there was a significant relationship between history of contact with patients, BCG immunization status, occupant density, house lighting, ventilation, nutritional status and family knowledge of pulmonary tuberculosis. This study suggests that the government, health agencies, and related parties collaborate to implement policies to reduce the risk of the spread of pulmonary tuberculosis in children. The community is advised to pay attention to hygiene, provide balanced nutrient intake and improve children's health status.